The UK Integrated Assessment Model for source apportionment and air pollution policy applications to PM2.5. (August 2021) - ApSimon, Helen; Oxley, Tim; Woodward, Huw; Mehlig, Daniel; Dore, Anthony; Holland, Mike
Highlights: We describe the UK Integrated Assessment Model applied to PM2.5 policy applications. We quantify exceedance of the WHO guideline in 2016. We quantify source contributions to PM2.5 concentrations in the UK. We define metrics, PWMC and PWME, which focus policy on the most exposed populations. We discuss uncertainties related to PM2.5 modelling. Abstract: Source apportionment and the effect of reducing individual sources is important input for the development of strategies to address air pollution. The UK Integrated Assessment Model, UKIAM, has been developed for this purpose as a flexible framework, combining information from different atmospheric dispersion models to cover different pollutant contributions, and span the range from European to local scale. In this paper we describe the UKIAM as developed for SO2, NOx, NH3, PM2.5 and VOCs. We illustrate its versatility and application with assessment of current PM2.5 concentrations and exposure of the UK population, as a case-study that has been used as the starting point to investigate potential improvement towards attainment of the WHO guideline of 10 µg/m 3 .